The Species Diversity and Structure of The Limited Production Forest in Arui Watershed of Manokwari District of West Papua, Indonesia - Mahmud, Mahmud; Kusumandari, Ambar; Sudarmadji, Sudarmadji; Supriyatno, Nunuk (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
The detailed causal factors of flood have not been established, whether because of the damage of upper watershed, sedimentation resulting in shallow river, forest conversion, the decrease in abundance and structure or high rainfall. The study aimed at finding out the species diversity and structure of the limited production forest (LPF) from the seedling to the tree stage of Arui watershed in Manokwari district. The species diversity was determined based on Shannon-Wiener index, while vegetation structure was determined based on Importance Value Index. There were totally 92 plots of samples drawn using systematic sampling. The results of vegetation analysis showed that there were 174 species of 43 families with the species diversity of 1.5-1.8 that was categorized as moderate. The four dominant species that were always found in seedling, sapling, pole and tree stages included: Pometia pinnata, Teijsmanniodendron bogoriense, Chisocheton ceramicus, and Horsfieldia irya. The conversion of the LPF into non-forestry sector for the purpose of accelerating development must be reviewed by considering hydrology, land, biodiversity, and social and regional aspects in order to prevent and to reduce flood in the coming days.